Handbook of mangroves in the Philippines, Panay (Southeast Asian Fisheries Development Center, Aquaculture Dept., 2004)
This handbook is a user-friendly presentation of technical botanical descriptions - terms are defined in the Glossary - and illustrations of Phillipine mangrove species in Panay Island, Guimaraas and Aurora Province.